A blockchain approach to digital archiving: digital signature certification chain preservation. (25th February 2020) - Bralić, Vladimir; Stančić, Hrvoje; Stengård, Mats
Abstract : Purpose: The short lifespan of digital signatures presents a challenge to the long-term preservation of digitally signed records. It can undermine attempts to presume, verify or assess their authenticity. This paper aims to investigate the challenges of the expiration of digital signatures in the context of digital archiving. Design/methodology/approach: The paper identifies requirements for the long-term preservation of digitally signed records and compares them with the existing approaches. The characteristics, operational procedures and requirements of the technologies used for digital signatures are combined with the archival requirements to design a new model. Findings: The paper proposes a new model of a blockchain-based system, which can be combined with any digital archive to assist the process of long-term preservation of digitally signed records. Practical implications: The proposed model offers a new alternative to the current practice in the long-term preservation of digitally signed records, such as periodic resigning procedures or periodic wrapping of digitally signed records with archival timestamps. Originality/value: The proposed TrustChain 2.0 model is based on previous research conducted as part of the InterPARES Trust project. It builds on TrustChain 1.0 by including digital signature certificate chain validity information in a blockchain thus avoiding the issues concerning records confidentiality and privacy information disclosure. The paper contributes not only to the development of archival science but also shows archival institutions on how to approach long-term preservation of digitally signed records.